Newsletter - Youth for Youth Québec (Y4Y Québec) (2021)
Number of pages: 12

Newsletter - Youth for Youth Québec (Y4Y Québec) (2021)
Number of pages: 10

Newsletter - Youth for Youth Québec (Y4Y Québec) (2021)
Number of pages: 11

Newsletter - Youth for Youth Québec (Y4Y Québec) (2021)
Number of pages: 13

Y4Y Québec Calls on the Legault Government to Consult with More Members of the English-speaking Community, and Youth in Particular, During Upcoming Bill 96 Hearings - Youth for Youth Québec (Y4Y Québec) (2021)

Protecting the Respiratory Health of Québec's Youth Population - Pattem, Alexandre (Youth for Youth Québec (Y4Y Québec), 2021)
Transportation traffic is one of the main sources of nitrogen dioxide (NO2), whether it emerges from trucks, buses, or car emissions (Government of Québec 2021). NO2 is formed from the “liberation of nitrogen contained in fuel and nitrogen contained in combustion air during combustion processes” (Government of Canada 2013). When released, NO2 has negative effects on human respiratory systems, especially those of teenagers and children (Wing, Sam E. et al 2018, 1-2). Growing evidence demonstrates that systems of asthma, for example, are likely to be aggravated or triggered in this youth segment of the population (Gillespie-Bennett, J. et al 2011, 303).

Newsletter - Youth for Youth Québec (Y4Y Québec) (2021)
Number of pages: 8

Newsletter - Youth for Youth Québec (Y4Y Québec) (2021)
Number of pages: 10

Le projet de loi 96 manque de perspective pour les jeunes et risque de créer de nouelles divisions entre les communautés linguistuques - Youth for Youth Québec (Y4Y Québec) (2021)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2021)
Number of pages: 10

Did the Black Lives Matter Movement Help English-speaking Black Young Adults in Quebec Recover from the Damaging Psychological Effects of the COVID-19 Pandemic? - Koestner, Richard; Holding, Anne C. (Quebec English-speaking Communities Research Network (QUESCREN), 2021)
The historic events of the spring of 2020—the collision of the worst public health crisis in a century and the largest Black civil rights movement in half a century—offer a unique opportunity to examine how the frustrations and hopes of English-speaking Black young adults were affected. We sought to understand the potentially competing impacts that the public health and social justice crises have had on the young adults in their communities. Quebec has the second largest Black population in Canada (after Ontario), with 27% of Canada’s total Black population. Quebec’s Black population has doubled in size in the past 20 years, with 325,000 people currently living here. This population is predominantly French speaking (80%), and it is concentrated in the Montreal metropolitan area (over 90%). The Black population tends to be younger than the Canadian average, and its members are more likely to be first-generation Canadians.
Parallel title: QUESCREN Working Paper no.4

Youth Volunteer Retention in Québec - Lopes-Luchak, Milla (Youth for Youth Québec (Y4Y Québec), 2021)
Volunteers are major contributors to nonprofit organizations in Québec and across Canada. Despite their contributions, studies reveal that volunteer retention is an aspect that remains neglected (Merrilees, Miller & Yakimova, 2020). There are many reasons why people give their time and remain in the same nonprofit. Consequently, there is no individual factor that guarantees retention; it differs depending on age group, gender, socio-economic background, area of volunteerism, etc. Improving retention is in the best interest of nonprofits. Although youth are the age group that volunteer the most (according to Volunteers Canada), Québec is the province with the lowest rate (as stated by statcan) and has much to learn from the rest of the country.

Newsletter - Youth for Youth Québec (Y4Y Québec) (2021)
Number of pages: 11

Newsletter - Youth for Youth Québec (Y4Y Québec) (2021)
Number of pages: 9

Supporting Youth Mental Health in and through the Arts : An Evidence Base and Guide for Teaching Artists - Kukkonen, Tiina (2021)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2021)
Number of pages: 6

L'exode des jeunes anglophones du Québec - Ciamarra, Nadine; Lamarre, Patricia; Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2021)
Parallel title: Résumé de recherche en éducation no 7
Keywords: Official Language Minority Community (OLMC)

Outmigration of Quebec's English-speaking Youth - Ciamarra, Nadine; Lamarre, Patricia; Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2021)
Parallel title: Education Research Brief no. 7
Keywords: Official Language Minority Community (OLMC)

Communauté du CHSSN NetLink - Community Health and Social Services Network (CHSSN) (2021)
Number of pages: 10

Community NetLink - Community Health and Social Services Network (CHSSN) (2021)
Number of pages: 6

Annual Report 2020-2021 - Youth Employment Services (YES) (2021)
As a not-for-profit organization, YES enriches the community by providing English-language support services to help Quebecers find employment and start and grow businesses. YES Employment + Entrepreneurship has been broadening access to opportunities for Quebec’s English-speaking community for over 25 years now. As we reflect on the organization’s 25th anniversary in the midst of the pandemic, we are reminded of the vital importance of our career and business support services.

Rapport annuel 2020-2021 - Youth Employment Services (YES) (2021)
En qualité d’organisme sans but lucratif, YES contribue à l’enrichissement de la communauté en offrant des services de soutien en anglais pour aider les québécois à trouver un emploi ou démarrer ou développer leurs entreprises. Depuis plus de 25 ans, YES Emploi + Entrepreneuriat facilite l’accès à différentes opportunités de croissance auprès de la communauté d’expression anglaise du Québec. Célébrer le 25e anniversaire de notre organisation en pleine pandémie nous rappelle à quel point nos services d’accompagnement à l’emploi et d’aide aux entreprises sont d’une importance vitale.

Annual Report 2020-2021 - Youth for Youth Québec (Y4Y Québec) (2021)